Multi Level Filantropi Islam (MLFI): Kerangka Operasional Distribusi Harta untuk Kesejahteraan Umat - Arin Setiyowati (Universitas Muhammadiyah Surabaya, 2022)
AbstractThe key issue of the economy is inequality. The offer of conventional economic theories proved unable to answer the problem. This paper aims to analyze the operational framework for the distribution of treasures from the Nash Qur'an in an effort to scientificize Islam and make Islam as a solution to the economic problems of the ummah. By using the study of literature in the formulation of multi-level theoretical islamic philanthropy (MLFI). The results of this study show that the Concept of Multi-Level Islamic Philanthropy (MLFI) as a viable operational framework to support fast and targeted for equitable welfare of the ummah. Both for the instrument of distribution that besifat mandatory and sunnah. So that it becomes a practical guide in determining the radius of benefit over the multiplier effect of income and distributed property.Keywords: Philanthropy, Distribution of Property, Welfare of The People